2019
DOI: 10.1111/jac.12337
|View full text |Cite
|
Sign up to set email alerts
|

Forage legumes for future dry climates: Lower relative biomass losses of minor forage legumes compared to Trifolium repens under conditions of periodic drought stress

Abstract: Dairy livestock production systems rely on high‐quality forage legumes, which are widely present in grassland swards all over Europe. A future climatic scenario with higher average annual temperatures and lower precipitation is expected to affect grassland productivity in general and the productivity of the most important forage legume species Trifolium repens in particular. One way to cope with such constraints is the adoption of currently underutilized minor legume species with a higher tolerance towards dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 54 publications
4
9
0
Order By: Relevance
“…Our drought resistance experiment confirmed previous research (Döring et al, 2013;Storkey et al, 2015;Elsalahy et al, 2019;Komainda et al, 2019) that BM is more drought-resistant than AC. Relative to the maximum biomass potential, which was higher in AC than in BM, the biomass under constant drought conditions was similar in both species, so that the relative biomass-reducing effect of drought was stronger in AC than in BM (Figure 1A).…”
Section: Effects Of Species Identity and Mixing On Drought Resistancesupporting
confidence: 91%
See 2 more Smart Citations
“…Our drought resistance experiment confirmed previous research (Döring et al, 2013;Storkey et al, 2015;Elsalahy et al, 2019;Komainda et al, 2019) that BM is more drought-resistant than AC. Relative to the maximum biomass potential, which was higher in AC than in BM, the biomass under constant drought conditions was similar in both species, so that the relative biomass-reducing effect of drought was stronger in AC than in BM (Figure 1A).…”
Section: Effects Of Species Identity and Mixing On Drought Resistancesupporting
confidence: 91%
“…In both experiments, water use efficiency (WUE, in g DM L −1 ) was determined by using Equation (1) (Komainda et al, 2019).…”
Section: Calculation Of Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…A area and g Sarea values of BAM measured at day 46 (that was not the point of maximum drought stress) were associated with higher leaf RWC (Foster et al, 2015) which confirms the drought adaptation of this variety (Foster et al, 2013). In agreement with the results of this study, previous research has found little or no effect of moderate drought stress on the quality parameters of forage legumes (Komainda et al, 2019;Kuchenmeister, Kuchenmeister, Kayser, Wrage & Isselstein, 2013).…”
Section: Nutritive Valuesupporting
confidence: 90%
“…We chose alsike clover (AC; Trifolium hybridum L.) and black medic (BM; Medicago lupulina L.) and a 1:1 mixture of the two species as previous studies showed a positive mixture effect of these two species at this proportion regarding productivity, weed suppression, and resilience to drought ( Elsalahy et al, 2019 ; Elsalahy et al, 2020 ). BM is a fast-growing perennial well adapted to warm and dry areas ( Döring et al, 2013 ; Elsalahy et al, 2019 ; FAO, 2020 ; Komainda et al, 2019 ) with a base temperature of 0.6 °C and optimal germination temperature of 26 °C ( Tribouillois et al, 2016 ). Nonetheless, it was also reported for BM that the optimal range of temperatures lies between 10 °C and 20 °C ( Sharpe & Boyd, 2019 ).…”
Section: Introductionmentioning
confidence: 99%